Commercial CaO Catalyzed Biodiesel Production Process - Abdel-Rahman, Zaid Adnan; Wiheeb, Ahmed Daham; Jumaa, Marwa Majeed (Al-Nahrain Journal for Engineering Sciences, 2017)
Biodiesel produced from vegetable oils is a good alternative clean diesel. The present study was conducted because there are some variations or contradictions in literature on the use of CaO heterogeneous catalyst. In this study, biodiesel was produced from sunflower vegetable oil and methanol in presence of commercial calcium oxide catalyst in batch mechanical stirrer reactor. The effect of three operating conditions, methanol mole ratio (4-12), reaction time (0.5-2.5 h) and catalyst amount (2-10 %), on the yield of biodiesel was studied at constant reaction temperature of 60 oC. Response surface methodology (RSM) was used with central composite design (CCD) of experiments. Polynomial correlation was found for the dependent variable of the process (yield of biodiesel), satisfactorily predicted at 95% confidence level. The optimum yield biodiesel was about 98% and at operating condition of methanol ratio 10, reaction time 2 h and catalyst amount 8 %. The reaction time was found to be the most effective operating condition. Kinetics study of the process showed that first order reaction with triglyceride concentration and zero order with methanol concentration gave best fit with the experimental data, triglyceride with a reaction rate constant k= 1.53 h-1.